Not Talking Union: An Oral History of North American Mennonites and Labour - Thiessen, Janis (McGill-Queen's University Press, 2016)
This book investigates the labour history of a people who have not been involved in the twentieth-century labour movement in large numbers: North American Mennonites. It explores their historically-constructed attitudes toward organized labour and unions, which it attempts to understand on its own terms. Although Mennonites are typically associated with rural life, they in fact became very involved as workers in specific locations in both traditional Mennonite enclaves in Ohio, Indiana, Ontario, and Manitoba, and those to which they migrated in the twentieth century, such as British Columbia and California. Mennonites in these locales found employment both as field workers for large agri-business operations (for example, the orchards and packing plants of the San Joaquin Valley in California) and as factory hands in manufacturing firms (such as the automotive factories in southern Ontario). The late twentieth century experiences of North American Mennonites in these settings caused them to confront and reassess their attitudes toward unions. A study of these Mennonites–united by transnational ties of ethnic and religious identity yet shaped, at times, in distinct ways by their differing geographic locations, immigration histories and ethnic origins, denominational ties, and class positions–provides insights into how and why the majority of North American Mennonites have rejected labour unions in the late twentieth and early twenty-first centuries. The oral histories of the 113 Mennonites interviewed provide insight into why many working North Americans are not union supporters, and how people in general negotiate tensions between their commitments to faith and conscience and the demands of their employment. An important aim of the book is to bring labour historians and historians of religion into conversation. –Publisher's description
OCLC: 952565535